Dental Cervical Lesions: How the Etiologies Imply in Different Approaches for Long-Lasting Performance - Zabeu, Giovanna Speranza; Mosquim, Victor; Bastos-Bitencourt, Natália Almeida; Santin, Daniella Cristo; Agulhari, Maria Angélica Silvério; Wang, Linda (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Particularities of dental cervical lesions require distinct approaches from preventive to therapeutic managements. Therefore, practitioners depend on their etiology, selected materials and patient involvement to provide conditions to effective performance. Through representative clinical scenarios, the main considerations regarding carious and non-carious cervical lesions (NCCL) are reported for the determination of strategies. Details regarding the disease, lesions aspects, evolution and involvement or not of the periodontal tissues are considered in their decision. In conclusion, their long-lasting resolution is determined by a complex combination of biomechanical factors and therapeutic strategies for each particular lesion, regardless of the cervical location solely.